Classroom support for students' digital literacy skills for learning in Tanzania's public universities. Issue 7 (3rd October 2022) - Nalaila, Stephano; Wawire, Violet; Gathara, Peter Mugo
ABSTRACT: This paper explores classroom support for students' acquisition of digital literacy skills for learning at the University of Dar es Salaam and Sokoine University of Agriculture in Tanzania. The paper contains qualitative data collected through questionnaires and informal discussions. The study found limited classroom support for students' digital literacy skills for learning because instructors are not prepared for it. Teaching activities that instructors implement do not reflect the attributes of digital literacy skills students should possess. Therefore, the paper challenges universities to mainstream students' digital literacy skills and train instructors to assume the skills support role.